Making Faces - Helen Chittock; Andrew Jones (Current Swedish Archaeology)
This paper examines the interplay between representational and non-representational art in later prehistoric Europe, aiming to form a starting point for more detailed and expansive study on this topic. We will approach later prehistoric imagery from an angle that has not been extensively explored, focusing on the deliberate use of ambiguity and the occasional appearance of representational images – particularly human bodies and faces – against a background of predominantly abstract and geometric imagery. We will hone in particularly on the imagery of Neolithic Britain and Ireland and the imagery of the European Iron Age, drawing on examples from existing research to establish new questions, and focusing especially on the affective potentials of faces and other bodily elements in later prehistoric imagery. We argue that images should always be viewed as being ‘in the making’ and we consider how Neolithic and Iron Age images became representational, emphasizing their emergent and ambiguous characteristics.